MARRIAGE REGISTRATION AND SOLEMNIZATION AMONG MIGRANT MUSLIMS IN GERMANY: Harmonizing Islamic and State Law and the Existence of Origin Country Law - Wahib, Ahmad Bunyan (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This article highlights the way of Islamic and state law intersect in the context of marriage administration and solemnization among migrant Muslim groups in Germany, with a particular emphasis on the coexistence of Islamic law and state law. The differences between the two legal systems are well known, with Islamic law being religious in nature and German law being secular. However, the article argues that interviews with two Turkish and Egyptian mosque imams in Göttingen reveal a harmonious relationship between the two legal systems. It sheds light on the ways in which these legal systems can complement each other and work together in harmony, despite their differences. The harmony between Islamic law and state law in Germany is linked to the context in which these legal systems are implemented, including their nature, place, time, and manner. The flexible and adaptable nature of Islamic law means that it can negotiate and adapt to state law depending on the circumstances. At the same time, the religious practices carried out by immigrant Muslim communities in Göttingen also reflect the presence of the law of their countries of origin.[Artikel ini membahas tentang praktik administrasi perkawinan yang dilakukan oleh kelompok minoritas Muslim di Jerman dengan fokus pada keberadaan hukum negara dan hukum Islam. Meskipun kedua system hukum ini mempunyai aturan yang berbeda secara substansi dan procedural, hasil wawancara dengan dua Imam masjid komunitas Turki dan Mesir di Goettingen menunjukkan adanya hubungan yang harmonis antara kedua system hukum tersebut. Harmoni yang terjadi antara hukum Islam dan hukum negara di Jerman ini berhubungan dengan watak, tempat, waktu, dan cara kedua system hukum ini dilaksanakan. Watak dan karakter hukum Islam yang lentur/fleksibel berkaitan dengan waktu dan tempat pelaksanaan, menjadikan hukum Islam mampu bernegoisasi dan beradaptasi dengan hukum Negara. Pada level tertentu, tata cara praktik keagamaan yang dilakukan oleh komunitas immigrant Muslim di Goettingen ini juga mencerminkan/membawa keberadaan hukum negara asal Muslim imigran.]